اثر الهيكل التنظيمي على الفاعلية التنظيمية - رانية, بن قدور; شيماء, نوي; امينة, نوي; روميصاء, شبابي (University of eloued جامعة الوادي, 2022)
"ملخص الدراسة هدفت هذه الدراسة إلى التعرف على أثر الهيكل التنظيمي على الفاعلية التنظيمية في المؤسسة العمومية ،تحقيق اهداف الدراسة تم استخدام المنهج الوصفي التحليلي وذلك بالاعتماد على مصادر البيانات الثانوية والأولية وقد تم تصميم استبانة كأداة لجمع البيانات و تم توزيعها على عينة قدرت ب (35 ) مفردة من مجموع الموظفين العاملين بدائرة جامعة والبالغ عددهم (42) موظفًا العاملين في المستويات الإدارية العليا والوسطى، وبعد التدقيق تم خضوع (33) استبانه للتحليل من مجموع الاستبانات الموزعة ، وتم تحليلها باستخدام البرنامج الإحصائي (spss ) وقد أظهرت نتائج الدراسة وجود أثر ذو دلالة إحصائية للهيكل التنظيمي على الفاعلية التنظيمية، واستنادًا على النتائج فقد أوصت الدراسة لعدد من التوصيات من أهمها : ضرورة أن تعمل المنظمة على تطوير الهيكل التنظيمي الخاص بها ليتوافق مع طموحات العاملين ضرورة أن تلتزم المنظمة بالتخصصات الوظيفية وفق الهيكل التنظيمي الخاص ، ضرورة وجود المرونة في الهيكل التنظيمي لتسريع وتيرة الأداء بالمنظمة ، دراسة أبعاد هيكلية أخرى ( كتفويض الصلاحيات ، نطاق الإشراف ، المرونة ) وتأثير هذه الأبعاد في الفاعلية التنظيمية . "" Study summary This study aimed to identify the impact of the organizational structure on organizational effectiveness in the public institution, to achieve the objectives of the study, the descriptive analytical method was used, depending on secondary and primary data sources. The total number of employees working in a university department is (42) employees working in the upper and middle administrative levels. After checking, (33) questionnaires were subjected to analysis from the total distributed questionnaires, and they were analyzed using the statistical program (spss). The results of the study showed a statistically significant effect of the structure Based on the results, the study recommended a number of recommendations, the most important of which are: The need for the organization to work on developing its own organizational structure to comply with the aspirations of the employees. The need for the organization to adhere to the functional disciplines according to the special organizational structure. The need for flexibility in the organizational structure to speed up the pace of performance in the organization. Studying other structural dimensions (such as delegation of powers, scope of supervision, flexibility) and the impact of These dimensions are in organizational effectiveness. "
ماستر ادارة اعمال
Keywords: الهيكل التنظيمي ، الفاعلية التنظيمية ، المركزية ، التخصص ، التعقيد ، الرسمية .; Organizational structure, organizational effectiveness, centralization, specialization, complexity, formality.